Environmental Health Narratives : A Reader for Youth - Koon, Adam, 1983-; Mendenhall, Emily, 1982- (Book collections on Project MUSE., 2012)
Written to draw attention to problems and solutions in environmental health across the world, the stories in this collection are about young people trying to make sense of the complex environments in which they live.